Research progress on the application of mobile health in weight management of pregnant and postpartum women (移动医疗在孕产妇体质量管理中的应用现状) - ZHANG Jiayu (张佳宇); TAO Yuexian (陶月仙); ZHOU Qi (周琪); ZHANG Na (张娜) (中西医结合护理)
Weight management is considered as an important contributor of healthcare during pregnancy and the postnatal period. Mobile health (mHealth) technology has the potential to play a key role in improving the health of patients with chronic diseases. This article provides an overview of the current status of mHealth applications in maternal weight management, lists the advantages and limitations of mHealth tools, and provides a reference for the development of mHealth tools in China and for the promotion of maternal weight management. (孕妇的体质量管理是妊娠期重要的环节。移动医疗(mHealth)技术作为治疗许多慢性病的辅助手段正变得越来越普遍。本研究综述mHealth在孕产妇体质量管理中的应用现状, 以期为国内开发移动医疗工具并为促进孕产妇体质量管理提供参考。)